Reinterpretation of Azolla primaeva (Azollaceae, Eocene, Canada) using electron microscopy and X-ray tomographic microscopy - Collinson, Margaret E.; van Konijnenburg-van Cittert, Johanna H.A.; Marone, Federica; Brain, Anthony P.R. (2017)
Azolla primaeva (Penhallow) Arnold fertile whole plants from the lower Eocene of Driftwood Creek, Canada have been examined using LM, SEM, TEM and SRXTM methods on hand specimens and sieved residues. The new data have resulted in an emended diagnosis. The megaspore is partly covered by filosum and the wall lacks excrescences. The exoperine is highly variable with nodular, to clavate, baculate and tabulate elements, which fuse to form a foveolate to reticulate megaspore surface, which is complex and contorted. Glochidia on the microspore massulae are sometimes septate and the flukes on their anchor-shaped tips are variable, some being long, narrow and wavy, others shorter and broad and a few are recurved. Hairs are lacking on the massula surface and glochidia. The organization of the float zone of the megaspore apparatus has always been controversial with 0, 1, 3 or 9 floats proposed. The new results show that there are no pseudovacuolate floats. By contrast, the ‘float’ zone consists of bundles of modified granular and filamentous endoperine elements surrounded by bundles of broader suprafilosum hairs. The absence of pseudovacuolate floats in A. primaeva is suggested to be an important character for phylogenetic analyses. The high variability in glochidia tips, glochidia septa and exoperine organisation is unusual within the genus Azolla. The new data on A. primaeva are compared with the other two whole plant Azolla species from Canada (Azolla stanleyi and Azolla schopfii) and with dispersed Azolla reproductive structures from Canada including the Arctic. This confirms that all are distinct species.